Law as a Tool of Social Engineering in Indonesia: Revisiting Roscoe Pound Theory and Its Application to Legal Reform - Chandra, William; Hamonangan, Marcellius Kirana; Rasji, Rasji (Journal of Business, Management, and Social Studies, 2024)
This article examines the role of law as an instrument of social engineering within the framework of sociological jurisprudence, focusing on its application in the Indonesian legal system. The study employs a normative juridical approach with conceptual, historical, and comparative methods to analyze how legal structures can influence social transformation. Findings indicate that while the theoretical foundation aligns with Indonesia’s aspiration for justice and reform, practical implementation often lacks systemic integration and responsiveness to societal needs. By mapping these gaps, the research proposes a conceptual framework for enhancing the law’s role in achieving equitable and adaptive legal reform. This contribution bridges classical legal theory with the realities of Indonesia’s legal development, highlighting the importance of aligning philosophical ideals with practical governance.